Literasi Digital Berbasis Nilai Islami Sebagai Jawaban Terhadap Tantangan Globalisasi Era Revolusi Industri 4.0 - Rosyid, Muhammad Iqbal; Aydalhaqq, Fathara; El Syam, Robingun Suyud (Paedagogie, 2026)
This article aims to analyze Islamic value-based digital literacy as a strategic solution to respond to globalization and maintain the moral integrity of students. The research method used is a literature study with a qualitative approach, examining various journals and studies related to digital literacy, Islamic education, and digital spiritual evaluation models. The research findings indicate that digital literacy in Islamic educational institutions is still diverse and uneven, with many teachers limited in using interactive digital platforms. The model of digital spiritual competence evaluation, which includes Islamic digital literacy, digital ethics, and the internalization of Islamic values, offers a tool to assess the extent to which Islamic values are applied in students' digital activities. The strategy for implementing Islamic digital literacy includes the use of interactive media, blended learning, teacher training, and adaptive leadership in Islamic education management. The main challenges include limitations in digital infrastructure, teacher competence, and the lack of systemic implementation of digital spiritual evaluation. The implications of this study emphasize that Islamic value-based digital literacy can enhance technological skills while strengthening the character, morals, and Islamic identity of students. With a structured implementation, Islamic education can serve as a moral fortress and an agent of transformation in facing digital globalization.